2016
DOI: 10.1093/rheumatology/kew422
|View full text |Cite
|
Sign up to set email alerts
|

Quality and acceptability of measures of exercise adherence in musculoskeletal settings: a systematic review

Abstract: Objective. To recommend robust and relevant measures of exercise adherence for application in the musculoskeletal field.Method. A systematic review of measures was conducted in two phases. Phase 1 sought to identify all reproducible measures used to assess exercise adherence in a musculoskeletal setting. Phase 2 identified published evidence of measurement and practical properties of identified measures. Eight databases were searched (from inception to February 2016). Study quality was assessed against the Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 58 publications
(99 reference statements)
2
62
0
1
Order By: Relevance
“…Three recent systematic reviews of measures of exercise and self-management methods for MSK pain14–16 found that measures of exercise adherence currently used within randomised controlled trials are highly variable (including questionnaires, diaries and class registers), lack evidence of a robust or considered development process and demonstrate inadequate psychometric properties for reliability and validity. There is no existing measure of adherence that is fit for purpose 14–16.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three recent systematic reviews of measures of exercise and self-management methods for MSK pain14–16 found that measures of exercise adherence currently used within randomised controlled trials are highly variable (including questionnaires, diaries and class registers), lack evidence of a robust or considered development process and demonstrate inadequate psychometric properties for reliability and validity. There is no existing measure of adherence that is fit for purpose 14–16.…”
Section: Introductionmentioning
confidence: 99%
“…Three recent systematic reviews of measures of exercise and self-management methods for MSK pain14–16 found that measures of exercise adherence currently used within randomised controlled trials are highly variable (including questionnaires, diaries and class registers), lack evidence of a robust or considered development process and demonstrate inadequate psychometric properties for reliability and validity. There is no existing measure of adherence that is fit for purpose 14–16. A valid and reliable measurement tool for adherence to TE for MSK pain is therefore required to enable interpretation of results from exercise trials and to robustly test the effectiveness of interventions intended to improve exercise adherence 13–16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compliance to exercises is a key outcome measure and a potential confounder when interpreting trial results that was not measured in the initial pilot. In the current literature, there is a lack of validated questionnaire that reliably measures exercises compliance or adherence (46). Compliance can be assessed in 2 different ways, either through patient reported measures or clinician assessment.…”
Section: Proposed Changes To Interventionmentioning
confidence: 99%
“…Compliance and adherence are key aspects in any exercises-based intervention for MSK conditions and having compliance measures allows for a more accurate interpretation of the results and form a signi cant part of the process evaluation (59). Unfortunately, there is no speci c measure for exercise adherence that has been proven to be high quality, relevant and acceptable (60). In order to give a holistic picture to adherence, the Sports Injury Rehabilitation Adherence Scale (SIRAS)(61) will provide the healthcare providers perspective while a self-administered questionnaire for patients has been designed to obtain patient's input (appendix).…”
Section: Compliance and Adherencementioning
confidence: 99%